Modified Surface Composition and Biocompatibility of Core-Shell Nitinol Nanoparticles Fabricated via Laser Ablation of Differently Passivized Targets - Dahiya, Ujjwal Ranjan; Singh, Sonu; Garg, Chetan Kumar; Rai, Aakansha; Kalyanasundaram, Dinesh (Frontiers in Materials, 2022)
Nitinol is a versatile alloy known for its shape memory effect and thus finds multiple applications in biomedical devices and implants. The biomedical applications of nitinol based devices are however limited due to concerns related to leaching and its associated cytotoxicity. Especially, nitinol nanoparticles despite being highly promising for biomedical applications like nanoactuators and biomolecular delivery agent are not explored owing to the same concerns. Moreover, nitinol nanoparticles (NP) and their biological interactions are not fully characterized and the available literature on their toxicity portrays a divided picture. Surface passivation of nitinol using multiple methods has been explored in the past to reduce leaching of nickel in implants while also improving the thrombogenic properties. In this work, we report the preparation of passivized nitinol NPs by laser ablation of nitinol targets, followed by different surface treatments. The effect of different treatments in reducing nickel leaching and its influence on biocompatibility was studied. Biocompatibility and multi-faceted interaction of nitinol NPs with osteoblast cells and associated toxicity were explored. Homogenous nitinol NPs were found to be generated at 25 W of laser power. Also, surface modification using hydrogen peroxide, anodization and acid etching were found to be effective in waning the nickel leaching and improving biocompatibility. In view of the observed results of cellular interactions we discuss the possible routes of cellular toxicity of these NPs. The prospective applications of such passivized NPs in the biomedical field are also discussed in this work.